THE IMPACT OF COVID-19 ON THE PROFITABILITY OF PUBLIC BANKS LISTED IN INDONESIA - Gracia S. Ugut; Emir Fauzi; Tri Oktavia Saraswati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Covid-19 has had a significant impact on the economy, especially the financial industry in developing countries such as Indonesia. This study attempted to investigate the effect of the Covivirus-19 pandemic on the profitability of Indonesian public banks. The sample consists of 41 banks registered on the Indonesian stock exchange between January 1, 2019 and December 31, 2021. The profitability of a bank is reflected by Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM), and TOBINs' Q. Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM), and TOBINs'Q are used as dependent variables in this study. The independent variables are asset size, deposits, and leverage from bank determinant factors, and exchange rates, interest rates, Gross Domestic Product (GDP), and new cases of Covid-19 per month from macroeconomic variables. The analysis revealed that Covid-19 has a negative impact on bank profitability, but only profitability as evaluated by NIM has a statistically significant negative impact. This study demonstrates that bank size or asset size, as well as interest rate, have a significant positive effect on the profitability of Indonesian banks that are publicly listed.